Effects of Different Stretching Routes on Microstructure and Mechanical Properties of AZ31B Magnesium Alloy Sheets. Issue 9 (September 2015) - Dong, Jingren; Zhang, Dingfei; Sun, Jing; Dai, Qingwei; Pan, Fusheng
<x xml:space="preserve">Abstract</x> AZ31B magnesium alloy sheets were stretched by 13% along three different routes: the extrusion direction (Route A), 45° to the extrusion direction (Route B) and the transverse direction (Route C), and then were annealed at 350 °C for 60 min. The microstructure and texture, tensile mechanical properties and formability were investigated at room temperature. The results indicated that all the three stretched samples exhibited weakened basal texture, compared with the as-received sheet due to static recrystallization. By comparison, Route B processed sample showed the most dispersive basal texture, while Route A processed specimen exhibited the lowest basal intensity. Improved mechanical properties for the stretched and annealed sheets with different stretching routes were achieved. Furthermore, Route A processed sheet showed the highest Erichsen value compared with the samples processed along Route B and Route C.